Applicability study on the degradation of acetaminophen via an H2O2/PDS-based advanced oxidation process using pyrite. (December 2018) - Peng, Shuhan; Feng, Yong; Liu, Yanxia; Wu, Deli
Abstract: H2 O2 - and PDS-based reactions are two typical advanced oxidation processes (AOPs) with different adaptive pH ranges. However, the underlying mechanisms that caused the distinct applicability of these two AOPs have rarely been explored. Herein, a comparative study of H2 O2 /PDS-based AOPs employing pyrite as a catalyst to degrade acetaminophen (ACT) was reported. The poor ACT degradation in H2 O2 /pyrite under alkaline conditions was proven to be caused by a lack of OH production instead of by the weaker oxidation property of OH. The continuous exposure surface behavior induced by the intense acid-production reaction between PDS and pyrite prevented the coverage of iron-containing compounds on the pyrite surface. Therefore, the adaptive pH range in PDS/pyrite could extend from 4 to 10, in contrast to the narrow effective pH range of 4–6 in H2 O2 /pyrite. Oxidant consumption indicated that H2 O2 /pyrite possesses a higher oxidation efficiency than PDS/pyrite. The homogenous catalytic effect was non-negligible in PDS/pyrite, whereas heterogeneous catalytic oxidation dominated H2 O2 /pyrite under acidic conditions. The quenching experiment and electron spin resonance (ESR) spectroscopy demonstrated that the dominant radical species in H2 O2 /PDS-based AOPs via pyrite at a pH of 4 were OH and OH/SO4 -, respectively, thus causing different degradation pathways of ACT. In addition, a higher proportion of S consumption was found in H2 O2 /pyrite, indicating that sulfur also plays a role during the catalytic reaction. The distinct surface reactions between pyrite and H2 O2 /PDS led to different water treatment applications. Highlights: Pyrite surface covered by Fe-oxide in alkaline cause low OH yield in H2 O2 /pyrite. Higher acid-yield favor the pyrite surface exposure in PDS/pyrite than H2 O2 /pyrite. ACT followed different degradation pathways in H2 O2 /pyrite and PDS/pyrite system.